A formação em serviço do tutor de educação a distância sob a ótica do pensamento complexo: a construção de uma identidade - Furtado, Valéria de Almeida (2009)
In 2002, the Secretary of Education for the State of Minas Gerais began implementation of the Teaching College Course, in the distance learning modality, which was denominated Veredas. The goal was to offer a university level course for professionals who work as teachers at the earliest grades of primary school. The analysis of the results, at the end of the course, showed that the objectives proposed were successfully achieved, considering that, of the 14,136 (fourteen thousand, one hundred and thirty-six) effectively enrolled teachers, 13,749 (thirteen thousand, seven hundred and forty-nine) acting teachers were trained at the higher education level. Eighteen (18) Educational Agencies or AFORs were created and the work in the Varginha (MG) Agency gave rise to the research that culminated in this thesis; it was connected to the University Center of Minas Gerais (UNIS). This research had two general objectives: to understand in-service training of optimized Distance Learning tutors through the reflection promoted, through the act of writing and by attainment of auto-heteroevaluative practice and to show the viability of the guiding principles proposed by the Complex Thought in education for in-service training of Distance Learning tutors and the signs of permanence of the transformations which have taken place in the period of this in-service training. The specific objectives were: survey bibliography in relation to the education of Distance Learning tutors; identify the existing relationships between Complex Thought, writing, assessment and education in in-service training of Distance Learning tutors in the Veredas Project of the AFOR/Varginha; show that the in-service training for Distance Learning tutors was focused on encouraging the auto-heteroevaluative process promoted through writing and the practice of the guiding principles of Complex Thought; and verify whether or not the changes that took place in the educational praxis, throughout the training of Distance Learning educational tutors, during the development of the Veredas Project in the AFOR/Varginha, remained after this program ended, using the reports that the tutors drafted during and following the end of this in-service training for this purpose. Considering that, according to the proposals of Complex Thought, the theory and method are two sides of the same movement and have a symbiotic relationship, transmuting without losing their specificity, the methodology used followed these steps: bibliographic survey aimed at a more profound study on the process of professional Distance Learning service education; detecting the existing relationships between the guiding principles-writing-assessment articulated in the formation of the tutoreducator s identity; and requesting that the 56 (fifty-six) tutor-educators who experienced the process of implementation and development of the Veredas Project (2002 to 2005) in the AFOR/Varginha, register their experiences as tutors for the Higher Learning Teacher Education Course Veredas, in the distance learning modality, in writing, focusing on vital aspects of the personal and professional dynamic. From these reports, 10 categories were chosen: learning; assessment; coordination; team experiences; growth; emotion; study; renewal; transformation; and life. Based upon these results it is possible to state that the triad of guiding principles of Complex Thought, the act of writing and the practice of auto-heteroevaluation constitute the cornerstones of the formation of the Distance Learning tutoreducator s identity in service. It is suggested that other studies be done with the goal of increasing the knowledge that has been crystallized here, as well as holding other teacher training courses, using the Veredas model